Advanced Design Approaches to Emerging Software Systems
DOI: 10.4018/978-1-60960-735-7.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Service Elicitation Method Using Applied Qualitative Research Procedures

Abstract: This chapter introduces QSE, the Qualitative Service Elicitation method. It applies qualitative research procedures in service elicitation. Service engineering practice lacks lightweight methods to identify service candidates in projects with tight schedules. QSE provides a systematic method to analyze requirement material in service-oriented systems development with a feasible effort. QSE uses the procedures of the grounded theory research method to elicit service candidates from business process descriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Categorizing the data from another case study [44] revealed that 77 % of the analyzed services (24 out of 31) and 92 % of the potentially reusable services (12 out of 13) were content services (type 1a). Sharing business data also seemed to be a major driver for service reuse in this case project.…”
Section: Summary Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorizing the data from another case study [44] revealed that 77 % of the analyzed services (24 out of 31) and 92 % of the potentially reusable services (12 out of 13) were content services (type 1a). Sharing business data also seemed to be a major driver for service reuse in this case project.…”
Section: Summary Of the Findingsmentioning
confidence: 99%
“…Different viewpoints can be combined with triangulation [45], to provide a business viewpoint to the phenomena of service reuse in enterprises: (1) The purpose of almost all services in the case ESB was to share data; (2) almost all potentially reusable services were related to sharing data in another case study [44]; (3) SOA adoption in general has been reported to improve data sharing [38,41,42]; and (4) runtime service reuse is mandatory to enable data sharing between service consumers [38]. All these viewpoints support the argument that data reuse provides enterprises motivation to pursue service reuse of data services.…”
Section: Summary Of the Findingsmentioning
confidence: 99%